2020
DOI: 10.1016/j.ajp.2020.102041
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental disorders in South Asia: An umbrella review of systematic reviews and meta-analyses

Abstract: Objectives: Mental disorders are highly prevalent in eight South Asian countries, yet there is a gap of a synthesized overview of the prevalence of mental disorders in this region. This umbrella review aims to summarize the prevalence of mental disorders from systematic reviews and metaanalyses of South Asian studies. Materials and methods: A systematic search of 11 major databases and additional sources was conducted until December 11, 2019. Articles were included if they were systematic reviews or meta-analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 55 publications
4
46
0
Order By: Relevance
“…In this umbrella review, studies receiving 0-4, 5-7, and 8-10 points were categorized as low-quality, medium-quality, and high-quality studies, respectively. The scoring and categorizing processes in this review were informed by earlier umbrella reviews [26,27,39].…”
Section: Search Querymentioning
confidence: 99%
See 1 more Smart Citation
“…In this umbrella review, studies receiving 0-4, 5-7, and 8-10 points were categorized as low-quality, medium-quality, and high-quality studies, respectively. The scoring and categorizing processes in this review were informed by earlier umbrella reviews [26,27,39].…”
Section: Search Querymentioning
confidence: 99%
“…Since 2015, many umbrella reviews have been conducted to evaluate the evidence base on the psychosocial epidemiology of mental health in diverse populations [22][23][24][25][26][27]. Although several reviews have reported psychological impacts of quarantine or isolation [28,29], no umbrella review or overview of the reviews was found, although such a review could provide valuable information on the mental health implications of quarantine and isolation within the global landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, many umbrella reviews have been conducted evaluating the evidence base on the psychosocial epidemiology of mental health in diverse populations [19][20][21][22][23][24]. However, no umbrella review or review of the reviews was found, which can inform the mental health implications of quarantine and isolation for infection prevention at the global landscape.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, South Asian countries including India have a high prevalence of mental disorders (Hossain et al, 2020b), where loneliness may impose further psychosocial burden among the affected individuals. Loneliness should be studied in the context of other mental disorders, especially among vulnerable individuals who have multiple coexisting mental disorders (Hossain et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%